1997
DOI: 10.1099/00221287-143-9-2913
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymorphism at the omp-31 locus of Brucella spp.: evidence for a large deletion in Brucella abortus, and other species-specific markers

Abstract: The omp-37 gene, encoding a major outer-membrane protein in Bnrcella melitensis, was PCR-amplif ied from Brucella strains representing all species and known biovars by using primers selected according to the B. melitensis 16M omp-37 published sequence. Amplification of omp-37 was achieved from DNA of all Bnrcella species with the exception of Brucella abortus, the only Brucella species where expression of omp-37 was not detected by reactivity with an mAb specific for an epitope located in Omp-31. Southern blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
74
1
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 30 publications
2
74
1
4
Order By: Relevance
“…The omp31 gene was PCR amplified and sequenced from all recognized Brucella species and biovar reference strains. The seven biovars of B. abortus were not included in this study, as they lack omp31 (36). The alignment of the Omp31 amino acid sequences, deduced from the determined nucleotide sequence, is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The omp31 gene was PCR amplified and sequenced from all recognized Brucella species and biovar reference strains. The seven biovars of B. abortus were not included in this study, as they lack omp31 (36). The alignment of the Omp31 amino acid sequences, deduced from the determined nucleotide sequence, is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the present work we have determined the nucleotide sequence of omp31 from all the Brucella species and biovar reference strains, with the exception of Brucella abortus, which lacks omp31 (36). We have shown that the nucleotide substitutions found in the B. ovis omp31 gene result in antigenic differences as measured by reactivity with MAbs specific for Omp31 and sera from B. ovis-infected rams.…”
mentioning
confidence: 99%
“…With the objective of improving the typing of these biovars, different PCR-based assays have been proposed. The most widely used are the PCR-restriction fragment length polymorphism (RFLP) analysis of genes omp2a and omp2b, which can differentiate between reference biovars 1, 2, and 3 (6), and of gene omp31, which is able to differentiate biovars 1 and 3 from biovar 2 (15). In addition, a modification of the original AMOS-PCR multiplex assay (4), including a new pair of primers derived from the ery locus (AMOS-ery-PCR [14]), can differentiate biovar 1 from others.…”
mentioning
confidence: 99%
“…Growth and harvesting of Brucella cells and bacterial DNA were performed as described elsewhere (2,8,12). All isolates were subjected to five different PCR-based typing techniques: PCR-RFLP analysis for omp2a, omp2b, and omp31 genes (6,15), multiplex AMOS-ery-PCR (14), and Brucella MLVA using 15 genetic markers (8,12). Figure 1 summarizes the molecular typing results and represents a dendrogram construct from MLVA genotyping assay data on the B. suis isolates.…”
mentioning
confidence: 99%
“…Bioinformatics research and planning genetic engineering studies were carried out using the Vector NTI 11.5 software package (Invitrogen, USA). Based on the studies of Vizcaino N. et al (38)(39)(40), the two most immunodominant regions of Brucella Omps were selected. The first region is in a position from 48 to 83 amino acids of Omp31, and the second one is in the position from 180 to 224 amino acids of Omp25.…”
Section: Methodsmentioning
confidence: 99%